Sphingosine-1-Phosphate and Macrophage Biology—How the Sphinx Tames the Big Eater - Weigert, Andreas; Olesch, Catherine; Brüne, Bernhard (Frontiers in Immunology, 2019)
The sphingolipid sphingosine-1-phosphate (S1P) is produced by sphingosine kinases to either signal through intracellular targets or to activate a family of specific G-protein-coupled receptors (S1PR). S1P levels are usually low in peripheral tissues compared to the vasculature, forming a gradient that mediates lymphocyte trafficking. However, S1P levels rise during inflammation in peripheral tissues, thereby affecting resident or recruited immune cells, including macrophages. As macrophages orchestrate initiation and resolution of inflammation, the sphingosine kinase/S1P/S1P-receptor axis emerges as an important determinant of macrophage function in the pathogenesis of inflammatory diseases such as cancer, atherosclerosis, and infection. In this review, we therefore summarize the current knowledge how S1P affects macrophage biology.